Evaluation of the Anti-Diabetic Activity of Paliasa Leaf Ethanol Fraction (Kleinhovia hospita L) Through Inhibition of the Enzymes α-Glucosidase and α-Amylase - Sarniati Rante Rura; Yulia Yusrini Djabir; Abdul Rahim; Sri Ningsih; Nisrina Firdausi (Sarana Ilmu Indonesia (salnesia), 2023)
Kleinhovia hospita has long been used to treat diseases, including diabetes mellitus. This study aimed to evaluate if the hypoglycemic effects of K. hospita extract and fractions were related to its inhibition on the activity of α-amylase and α-glycosidase enzymes. K. hospita leaves were extracted with 96% ethanol and then subjected to liquid-liquid partition using n-hexane, ethyl acetate, and water as solvents. The inhibitory capacity of ethanolic extract and its fractions were tested against α-amylase and α-glycosidase enzyme activity and compared to acarbose. The in vitro study revealed that the IC50 of ethanolic extract, hexane, ethyl acetate, and water fractions were 1496,8 µg/mL, 1266,7 µg/mL, 12577,5 µg/mL, and 5217,0 µg/mL, respectively, against alfa-amylase activity. Whereas, for α-glycosidase activity, the IC50 values were 1341,2 µg/mL, 25470,0 µg/mL, 64450,0 µg/mL, and 1291,4 µg/mL, respectively. These values were markedly greater than those of the acarbose (7,4 and 5,5 µg/mL, respectively). From the research results, it was concluded that K. hospita leaf extract had a high IC50 value from K. hospita extracts and fractions, which indicated that the hypoglycemic effect of K. hospita was not related to the inhibition of the α-amylase and α-glycosidase enzymes.